Effectiveness Of Digital Culture Services At Village Credit Institutions (Lpd Samsat) In Improving Motor Vehicle Tax Revenue At The Regional Revenue Agency Of Bali Province - Gusti Agung Ayu Komang Sriyanti; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The LPD Samsat Service with a Digital Culture is an innovation to provide easy service for the public to pay Motor Vehicle Tax. The existence of problems related to the effectiveness of the Samsat LPD service with a Digital Culture, is the background for this research to find out how effective it is, the factors that are obstacles and the efforts made to increase the effectiveness of the Samsat LPD service with a Digital Culture in increasing Motor Vehicle Tax revenue. This research uses a qualitative descriptive method approach. The results of the research show that improving Samsat LPD services with a Digital Culture in increasing Motor Vehicle Tax revenues at the Regional Revenue Agency of Bali Province, seen from the indicators of goal achievement, has been effective, but seen from the indicators of integrity and adaptation it has not been completely effective. The inhibiting factors are the lack of public understanding in utilizing Samsat services, where people still tend to pay Motor Vehicle Tax conventionally, there is still a minimal number of healthy LPDs who collaborate in terms of paying Motor Vehicle Tax, and they still often encounter The problem with the process of inputting data into the system is that two processes are still carried out, validating the STNK and printing the SKPDKB. Another obstacle is that internet access is still inadequate. The efforts made are to improve the quality of the internet network, to bring in the Police and Bapenda for the validation process, to take an inventory of healthy LPDs to collaborate with in terms of tax payments and to intensify the socialization of Samsat LPD services with a Digital Culture.